The art of cosplay and creative makeup : create incredible looks with simple techniques and affordable materials - Peck, Chris (Makeup artist) (Rockport Publishers, an imprint of The Quarto Group, 2024)
"In The Art of Cosplay and Creative Makeup, body painter extraordinaire Rainbowskinz show you the fundamental techniques he uses to create an infinite number of extraordinary looks."--